Does infertility history affect the emotional adjustment of couples undergoing assisted reproduction? the mediating role of the importance of parenthood - Ramos, Mariana Moura (2016)
The emotional adjustment of couples undergoing assisted reproductive technology (ART) treatments has been widely studied; however, it remains unclear whether infertility history contributes to couples' adjustment. This study examined the impact of infertility history (duration of infertility and number of previous ART treatment cycles) on the emotional adjustment of couples undergoing an ART cycle and the mediating effect of importance of parenthood on that association.